The Macak–Manak–Masak Philosophy: Is It Still Relevant in Determining Succession in Family Businesses in Tulungagung? - Vania Rabbanihasna Jatmiko; Metta Padmalia; Andrea Gideon (MASI Mandiri Edukasi, 2026)
This study aims to discuss the relevance of the Javanese cultural values of macak, manak, and masak in the process of family business succession to female successors. This study departs from the assumption that this philosophy still limits women’s roles to the domestic sphere, especially in the context of Javanese society, which is closely tied to patriarchal culture. The objective of this study is to analyze how the values of macak, manak, and masak are interpreted and implemented in the preparation and decision-making processes of family business succession. The study uses a qualitative case study design with five family businesses in Tulungagung Regency that have been operating across generations and involve female successors. Data collection techniques included semi-structured interviews, observations, focus group discussions (FGD), and source triangulation. The results of the study show that macak, manak, and masak are no longer the basis for the family business succession process. Four main themes were found, namely interest, independence, collaboration, and tradition. The interest of female successors is formed through early involvement and family support. Women’s independence develops in response to economic demands and to the need for business sustainability. Cross-generational collaboration occurs based on competence, not gender, while tradition is interpreted as the inheritance of moral values and family business identity. This study concludes that there has been a shift in values in family businesses.